Regional Resource Management as a Strengthening of the Role of Local Government in Merangin Regency - Ulfa, Santi Nofria; Frinaldi, Aldri; Magriasti, Lince; Naldi, Hendra (Universitas KH. Abdul Chalim Mojokerto, 2026)
Regional resource management is a crucial aspect in strengthening the capacity and independence of local governments in supporting sustainable development. This article analyzes the role of the Merangin Regency government in managing regional resources in Merangin Regency, which have the potential to support sustainable economic, social, and environmental development, such as in the agriculture, forestry, tourism, and mining sectors. However, the success of this management is still hampered by various challenges and obstacles, such as limited infrastructure, environmental damage, illegal activities, low local economic added value, and the weak capacity of local government institutions to optimally manage potential. Through a literature review method, this study emphasizes that effective resource management can improve community welfare and support regional development oriented towards ecosystem sustainability and community empowerment. Strengthening the role of local governments, including in spatial planning, human resource development, and intersectoral collaboration, is key to optimizing resource potential. Therefore, the success of resource management in Merangin Regency depends heavily on increasing institutional capacity and implementing effective, environmentally and sustainably oriented policies. These obstacles must be addressed comprehensively so that the resource potential in Merangin Regency can be optimally utilized to improve community welfare and the sustainability of its ecosystem.